2015
DOI: 10.1007/978-3-319-22834-1_9
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immune Recognition of EBV

Abstract: The ability of Epstein-Barr virus (EBV) to establish latency despite specific immune responses and to successfully persist lifelong in the human host shows that EBV has developed powerful strategies and mechanisms to exploit, evade, abolish, or downsize otherwise effective immune responses to ensure its own survival. This chapter focuses on current knowledge on innate immune responses against EBV and its evasion strategies for own benefit and summarizes the questions that remain to be tackled. Innate immune re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 101 publications
0
31
0
Order By: Relevance
“…Human monocytes express several TLRs reported to sense EBV products including TLR 8, whose expression can be strongly up‐regulated by EBV infection . TLR signaling has been shown to affect PD‐L1 expression, thus we next investigated whether the inhibition of TLR signaling by IRAK1/4 inhibitor could counteract such immune suppressive effect induced by EBV.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Human monocytes express several TLRs reported to sense EBV products including TLR 8, whose expression can be strongly up‐regulated by EBV infection . TLR signaling has been shown to affect PD‐L1 expression, thus we next investigated whether the inhibition of TLR signaling by IRAK1/4 inhibitor could counteract such immune suppressive effect induced by EBV.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that it down‐regulated TLR9 or up‐regulated TLR 7 in B cells, whereas in monocytes, it activated and increased the expression of TLR 8 . TLRs represent a family of PRRs widely expressed among the immune system cells, which plays an essential role in pathogen recognition; therefore, the modulation of TLR expression or activation represent a possible strategy to impair immune recognition . Interestingly, in addition to immune stimulating functions, TLR signaling may also mediate immune suppressive effects, including the up‐regulation of PD‐L1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that the main target cells of EBV are epithelial cells and B cells. [14] EBV could infect epithelial cells via apical to basolateral transcytosis. [15] Thus, the elevated EBV DNA in CSF may be due to the CNS EBV reactivation or the activated resident EBV-positive cells in the CNS by the local inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…While the adaptive immune response to EBV has been extensively analyzed, only more recently has the role of the innate immune system (25), and natural killer (NK) cells in particular (26), been addressed. NK cells are lymphocytes of the innate immune system that possess the ability to rapidly recognize and respond to virally infected cells via cytotoxic pathways or production of immunomodulatory cytokines, hence they are viewed as an initial line of defense following infection.…”
Section: Natural Killer Cells and Ebvmentioning
confidence: 99%